Mitigating facets of team knowledge hiding: A collaborative view of psychological safety and team embeddedness through the lens of COR theory - Hina Shahid; Faisal Qadeer; Albert John; Imran Hameed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Drawing from the conservation of resources (COR) theory as the overarching framework, this study develops a collaborative view on mitigating team knowledge hiding facets (i.e., evasive hiding, playing dumb, and rationalized hiding). It proposes team embeddedness as an attachment construct acquired through investment in team psychological safety. Such acquisition compels team members to protect and foster the state of resource abundance and subsequently acts as a deterrent against team knowledge hiding. Multi-wave and multi- level data was obtained from 520 team members nested in 104 teams employed in information technology (IT) firms - a knowledge-intensive service sector. The data was analyzed using multi-level structural equation modeling through Mplus. The findings indicate that having access to team social resources (team psychological safety) leads to team embeddedness, creating a gain spiral that motivates members not to indulge in evasive hiding and playing dumb. Additionally, the mediation effect of team embeddedness between team psychological safety and team playing dumb is further moderated by individual-level learning orientation. On the other hand, these variables do not significantly decrease rationalized hiding.
Keywords: 330; Multi-level analysis; team embeddedness; team psychological safety; evasive; hiding; playing dumb; rationalized hiding; learning orientation; IT industry